Improved accuracy of hemimandibular reconstructions involving the condyle by utilizing hydroformed reconstruction plates rather than hand‐bent stock plates. Issue 9 (28th May 2019) - Ong, Hui Shan; Liu, Jian Nan; Ahmed, Abdelrehem; Qu, Xing Zhou; Wan, Kenneth; Xie, Dong Ping; Zhang, Chen Ping
Abstract: Background: Computer‐aided design/computer‐aided manufacturing (CAD/CAM) surgical templates allow precise mandibular reconstructive surgery. However, their clinical accuracy is limited by manual plate bending. Digitally hydroformed plates maintain a digital workstream in virtual planning. Methods: Twelve patients with Brown's class IIc mandibular defects were randomized into two groups: group I (experimental), the reconstruction plate was digitally hydroformed, and group II (control), surgeries were performed CAD/CAM guided with the reconstruction plate manually prebent. The linear and angular deviations of reconstruction outcomes were compared to surgical simulation in both groups. Results: The mean linear and angular deviations of middle and posterior segments were 2.14 ± 0.79 mm, 3.71 ± 0.95 mm, 8.73° ± 1.91°, and 9.06° ± 0.96° in group I and 4.31 ± 0.78 mm, 6.74 ± 1.40 mm, 16.35° ± 0.72°, and 31.48° ± 3.38° in group II, respectively. Measurements in group I were significantly lower than group II ( P < .005). Conclusion: Digital hydroforming for plate prebent is a reliable method that helps improving the clinical accuracy of CAD/CAM‐guided mandibular reconstruction surgery.